Decarbonizing the Industry Sector and its Effect on Electricity Transmission Grid Operation - Implications from a Model Based Analysis for Germany - Martin Lieberwirth; Hannes Hobbie (ZBW - Leibniz Information Centre for Economics, 2022)
Integrating large amounts of electrolyzer capacities poses particular challenges for grid operators along the entire hydrogen value chain. This research examines how hydrogen production capacities that support the decarbonization of German industrial sectors impact the electricity transmission grid. The operation of electrolyzer capacities and the production of green hydrogen result in increased electricity demand that stresses the power grids beyond conventional electricity load levels. The question arises to what extent electrolyzer capacities cause additional grid congestion and how flexible operation of electrolyzers can contribute to efficient management of future power grids. A scenario framework is created, differing in the decarbonizing strategy of industry sectors, operation mode of electrolyzers, and penetration levels of electrolyzer installations for a market projection of the future European electricity system. Model-based research is performed by applying a fundamental electricity market and congestion management optimization model of the European electricity systems for the set of scenarios. Results of the model-based investigation highlight the importance of integrating electrolyzer capacities into congestion management practices, primarily if corresponding decarbonized industries feature a more distributed allocation throughout Germany, such as the chemical, paper and printing industries. The findings of this work provide policymakers, system operators, and regulators with meaningful insights for designing future congestion management frameworks.
Keywords: C61; Q41; Q48; 330; Electricity; Green hydrogen; Congestion management; Grid modelling; Germany